Inovasi Olahan Ikan Tuna menjadi Bakso Ikan bagi Pelaku Usaha Kuliner di Pariwisata Pantai Desa Botutunuo - Victorson Taruh; Lukman Pakaya (Universitas 45 Surabaya, 2025)
Gorontalo as a province that includes the Tomini Bay area, makes this area have residents who use the sea as a livelihood. Botutunuo Village as one of the nine villages located in Kabila Bone sub-district, Bone Bolango Regency, has its own attraction as a village located on the coast of the Tomini Bay area. Not only as fishermen, many culinary business actors use this coastal area as a place for beach tourism businesses. The service team saw the great potential of marine products obtained by fishermen, one of which was tuna. This community service aims to increase the income of culinary business actors, namely MSMEs who have stalls around the tourist area of Botutunuo village and share the knowledge of the service team in processing tuna into fish balls. The enthusiasm of culinary business actors in Botutunuo Village is illustrated by the attraction of the participants in listening and seeing the direct practices demonstrated by the service team. The results of this service are expected to be able to encourage increasing the income of fishermen and MSME culinary business actors in Botutunuo village to sell their goods to tourists who visit coastal tourist sites and help improve the welfare of the village community to increase their economic income.